2012
DOI: 10.1016/j.drugalcdep.2011.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Trazodone for sleep disturbance during methadone maintenance: A double-blind, placebo-controlled trial

Abstract: BACKGROUND To test whether trazodone, one of the most commonly prescribed medications for treatment of insomnia, improves subjective and/or objective sleep among methadone-maintained persons with sleep complaints, we performed a randomized, double-blind, placebo-controlled trial with six month follow-up. METHODS From eight methadone maintenance programs in the northeastern United States, we recruited 137 persons receiving methadone for at least one month who reported a Pittsburgh Sleep Quality Index (PSQI) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 41 publications
0
44
0
Order By: Relevance
“…Trazodone, approved by the FDA in 1981, is a serotonin antagonist and reuptake inhibitor (SARI) antidepressant that has been extensively prescribed for off‐label use as a treatment for insomnia. Findings from recent studies using other medications or placebo as control are mixed; trazodone was found to improve sleep among patients with primary and secondary insomnia, although it was not effective among methadone maintenance patients with insomnia . Trazodone has been shown to alleviate opioid and benzodiazepine withdrawal symptoms in dependent patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trazodone, approved by the FDA in 1981, is a serotonin antagonist and reuptake inhibitor (SARI) antidepressant that has been extensively prescribed for off‐label use as a treatment for insomnia. Findings from recent studies using other medications or placebo as control are mixed; trazodone was found to improve sleep among patients with primary and secondary insomnia, although it was not effective among methadone maintenance patients with insomnia . Trazodone has been shown to alleviate opioid and benzodiazepine withdrawal symptoms in dependent patients.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from recent studies using other medications or placebo as control are mixed; trazodone was found to improve sleep among patients with primary and secondary 18 insomnia, although it was not effective among methadone maintenance patients with insomnia. 19 Trazodone has been shown to alleviate opioid 20,21 and benzodiazepine 22 withdrawal symptoms in dependent patients. No systematic national data on trazodone abuse/misuse are apparent in the literature.…”
Section: Methodsmentioning
confidence: 99%
“…For example, actigraphy may be less accurate in measuring sleep latency and is prone to first night effects. Future research would benefit from the collection of more in-depth sleep quality data utilizing polysomnographic methods that alleviate first night effects and allow for assessment of sleep apneic events (Krystal & Edlinger, 2008; Kurth et al, 2009; Sharkey et al, 2011; Stein et al, 2012). Finally, future research may also be informed by the extension of the assessment timeframe and environment (i.e., to naturalistic home environment).…”
Section: Discussionmentioning
confidence: 99%
“…Additional symptoms on BSRS refers to poor appetite and sleep difficulty. Poor appetite and sleep difficulty are common symptoms and very highly prevalent in heroin users 29,30. Short sleep duration (<6 hours) is associated with poor physical and self-perceived mental health status, as well as increased morbidity and mortality 31,32.…”
Section: Discussionmentioning
confidence: 99%